2014
DOI: 10.1108/he-07-2013-0030
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review investigating the use of Twitter and Facebook in university-based healthcare education

Abstract: Purpose – The purpose of this paper is to evaluate the use, attitudes and perceptions of both teachers and students towards social media platforms (Facebook and Twitter) in healthcare higher education practice. Design/methodology/approach – Systematic literature review. A search of published and unpublished databases was conducted from January 2000 to January 2013. Data were synthesised through a narrative approach. All included studies were critically appraised using Critical Appraisal Skills Programme apprai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 32 publications
0
46
0
2
Order By: Relevance
“…Reviews have summarized social media use in education previously. However, they examined a range of online platforms, defined social media broadly (Bassell, 2010), had limited studies relevant to nursing and midwifery (Smith & Lambert, 2014), or adopted methodologically weak approaches (Arrigoni, Alvaro, Vellone, & Vanzetta, 2016;Gunberg Ross & Myers, 2017). Therefore, a gap exists in our understanding of how effective social media, especially SNSs, could be in supporting learning among nursing and midwifery students.…”
Section: Introductionmentioning
confidence: 99%
“…Reviews have summarized social media use in education previously. However, they examined a range of online platforms, defined social media broadly (Bassell, 2010), had limited studies relevant to nursing and midwifery (Smith & Lambert, 2014), or adopted methodologically weak approaches (Arrigoni, Alvaro, Vellone, & Vanzetta, 2016;Gunberg Ross & Myers, 2017). Therefore, a gap exists in our understanding of how effective social media, especially SNSs, could be in supporting learning among nursing and midwifery students.…”
Section: Introductionmentioning
confidence: 99%
“…In the academic setting, Smith and Lambert (2014) described Facebook as a platform to engage students. In their systematic review of the literature, they found limited research regarding the use of Facebook for educational purposes.…”
Section: Facebookmentioning
confidence: 99%
“…The synthesis efforts to date have typically adopted a sweeping, generalized definition of social media that includes all ranges of technologies, from wikis, to blogs, SNSs, podcasts, and other related online platforms (Bassell, ). Other reviews have limited studies relevant to nursing or midwifery (Smith & Lambert, ) or have applied weak methodological approaches (Arrigoni et al., ). Due to the uniqueness and higher level of communication fidelity afforded by SNSs, it was deemed important to generate a mixed study systematic review exploring the use of this particular form of social media in nursing and midwifery education.…”
Section: Introductionmentioning
confidence: 99%
“…To date, numerous descriptive articles have been published outlining a large array of social media technology and educational practices in relation to nursing and midwifery (Ashton, 2016;Clifton & Mann, 2011;Schmitt, Sims-Giddens, & Booth, 2012;Stewart, Sidebotham, & Davis, 2012), including more robust studies examining the use of social media in this literature (Booth, 2015;Kitching, Winbolt, MacPhail, & Ibrahim, 2015;Richardson, Grose, Nelmes, Parra, & Linares, 2016;Uppal, Davies, Nuttall, & Knowles, 2016). There has also been some past review efforts completed to synthesize how social media technology has been used to support mentorship activities between nursing faculty (Bassell, 2010); for health professional education in university settings (Smith & Lambert, 2014); and, in nursing education in general (Arrigoni, Alvaro, Vellone, & Vanzetta, 2016). Regardless, there is a current and sizable gap in synthesis of research exploring the efficacy, impact or value of social media in nursing and midwifery education.…”
Section: Introductionmentioning
confidence: 99%